2013
DOI: 10.1002/polb.23368
|View full text |Cite
|
Sign up to set email alerts
|

3‐D Interdigitated electrodes for uniform stimulation of electro‐responsive hydrogels for biomedical applications

Abstract: Stimuli‐responsive hydrogels are continuing to increase in demand in biomedical applications. Occluding a blood vessel is one possible application which is ideal for a hydrogel because of their ability to expand in a fluid environment. However, typically stimuli‐responsive hydrogels focus on bending instead of radial uniform expansion, which is required for an occlusion application. This article focuses on using an interdigitated electrode device to stimulate an electro‐responsive hydrogel in order to demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Based on these results an ideal IDT electrode would expand/shrink with the hydrogel, however this is difficult to achieve. Previous results demonstrated that an electrical bias does not significantly affect the swelling equilibrium level, as the ERH swells normally, once the biased is removed [9].The overall results from the in vitro electro-actuation experiment validate the concept that an IDT electrode configuration can slow down expansion of the hydrogel. Therefore, an IDT electrode configuration integrated into a delivery system could be used for operations that require longer insertion times.…”
Section: A Characterization Of Electro-responsive Hydrogelsupporting
confidence: 62%
See 4 more Smart Citations
“…Based on these results an ideal IDT electrode would expand/shrink with the hydrogel, however this is difficult to achieve. Previous results demonstrated that an electrical bias does not significantly affect the swelling equilibrium level, as the ERH swells normally, once the biased is removed [9].The overall results from the in vitro electro-actuation experiment validate the concept that an IDT electrode configuration can slow down expansion of the hydrogel. Therefore, an IDT electrode configuration integrated into a delivery system could be used for operations that require longer insertion times.…”
Section: A Characterization Of Electro-responsive Hydrogelsupporting
confidence: 62%
“…The dried samples were 3 mm in diameter where as the IDT electrodes have a configuration diameter of approximately 6 mm. The depth of the electric-field from the IDT in this case was previously shown to be shallow [9]. As the hydrogel expands it becomes closer to the electrodes thus increasing the impact of the applied electrical bias.…”
Section: A Characterization Of Electro-responsive Hydrogelmentioning
confidence: 91%
See 3 more Smart Citations